Investigation into the effect of small molecule inhibitors on glioma cell migration - Zara Ahmed (Fields, 2023)
This study aimed to observe the effect of anti-migratory drugs on glioblastoma (GBM) cell migration by targeting key pathways in migration, including actin polymerisation and RhoA – all of which channel cell migration. GBMs are a form of brain tumour originating in the brain in which they infiltrate surrounding brain tissues. Due to the invasive nature of glioma cells, treatment is difficult, resulting in current treatment options remaining ineffective in enhancing GBM survival rates. Cell migration plays an essential role in the invasion of GBM cells – ongoing research has revealed that targeting migratory pathways may be a complementary, novel treatment option as anti-migratory drugs may be used to inhibit cell migration and prevent cancer cell invasion in GBMs. This study aimed to gather further evidence for the use of anti-migratory drugs by investigating in vitro experimental methods for the assessment of a panel of anti-migratory inhibitors (CCG-1423 and Rhosin Hydrochloride) in the established U87 glioma cell line. The methodology comprised immunofluorescence staining whereby the morphology (roundness) of cells and Corrected Total Cell Fluorescence (CTCF) of cellular actin was observed and analysed using ImageJ-Fiji software. CTCF results revealed that the use of CCG-1423 and Rhosin Hydrochloride (HCl) studied in combination were statistically significant to controlled-treated cells (p = 0.0037). The roundness of U87 cells illustrated a significant difference between Rhosin HCl-treated cells (p = 0.001) and combination-treated cells (p = 0.0037) compared to the control. Morphological analysis revealed novel findings with the use of CCG-1423 and Rhosin HCl utilised in combination for U87 gliomas – cells exhibited an alternative mode of migration, collective migration, in addition to mesenchymal or amoeboid migration. As such the use of CCG-1423 and Rhosin HCl in combination may trigger a third signalling pathway enabling collective migration. Crucially, the use of combination treatment for GBM allows the breakthrough for novel research to be examined further as combination drugs may pose therapeutic benefits in hindering glioma cell migration.